(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article analyzes the stories "Muz Kongil" and "Yol" composed by Sotim Avaz, a child of the Khorezm individuals, additionally talks almost the pith of the story, composing aptitudes, and characters.